DEVELOPING FOOTWEAR BUSINESS: WHAT IS THE STRATEGY? - Novi Marlena; Renny Dwijayanti (Fakultas Ekonomi Universitas Negeri Jakarta, 2018)
Nowadays one promising business is the fashion industry, especially footwear. UD. Poker is one of the Small and Medium Enterprises which engaged in the footwear industry. This research is descriptive using a qualitative approach. Data collection techniques using in-depth interviews directly with the owners, employees, and communities around UD. Poker. Depth interviews, observation, and documentation are also used in data collection. Data analysis techniques used in this study consisted of four stages, 1) analysis of internal and external environment UD. Poker, 2) analyzing using the SWOT matrix, and 3) formulating alternative strategies, 4) recommending strategic decisions to develop business for UD. Poker. Based on the SWOT matrix program, the position of UD Poker is in quadrant I (aggressive strategy) which means that UD Poker is growing so UD. Poker is more appropriate to implement the Strength Opportunity (SO) strategy through market penetration and product development.